An Overworked Leave? Health Care Workforce Effects of Brexit - Joan Costa-Font; Cristina Vilaplana-Prieto (CESifo GmbH, 2025)
We study the impact of the Brexit referendum on the quality of employment and working conditions of workers in the National Health Service (NHS). Using a difference-in-differences (DiD) design and propensity score matching to compare NHS employees with a control group referring to occupations less exposed to employees from the European Union (EU) before Brexit. We document that Brexit led to the average reduction of job satisfaction by 1.39% - largest for physicians (2.6%) and nurses (2.4%) - and an increase of both paid (1.75 hours/week) and unpaid working hours (8.3 hours/week). Nonetheless, the effect was heterogeneous despite the general rise in working time. Indeed, job satisfaction fell by 2.6% among British workers but increased by 3% among overseas workers. These changes were accompanied by a comparable reduction in leisure time and a higher likelihood of workers intending to leave their jobs, suggesting broader behavioural effects that may undermine NHS productivity.
Keywords: I12; J22; J45; 330; job satisfaction; workforce motivation; Brexit; health care workforce; workforce composition; leisure satisfaction; NHS